PB6 Antimicrobial stewardship education and effect on prescribing in the emergency department of an irish teaching hospital. (19th March 2012) - Foley, S; James, K; Fitzpatrick, F
Abstract : Objectives and Background: Careful selection of antimicrobials is imperative in preventing adverse events and resistant organisms. Guidelines and their availability encourage appropriate prescribing. In our centre, the microbiology team present bi-annually in the Emergency Department (ED) on topics related to the prudent use of antibiotics. This audit aimed to assess compliance with hospital antimicrobial guidelines in medical patients admitted via the ED. Method: A prospective audit was conducted from 01 September 2010 to 30 September 2010. All medical patients were eligible to be included. Data were extracted from patients' notes and drug Kardexes. The audit identified members of staff involved in prescribing antibiotics and their respective compliance with current antimicrobial guidelines as published by the Microbiology Department. Results: 101 medical patients (52 female, 49 male) were included (mean age 65 years). Nine (8.9%) patients did not have an "allergy status" documented. The majority of antimicrobials were prescribed by ED senior house officers (SHOs) and registrars (69.3%). Medical SHOs or registrars prescribed in 28 (27.7%) cases and in 3 (2.9%) patients, the prescriber was unidentified. The rates of compliance with antimicrobial guidelines are detailed in Abstract PB6 table 1 . 147 antibiotics were prescribed and 22 different conditions were listed as the indication for therapy. Conclusion: Bi-annual education sessions regarding antimicrobial prescribing provided by the Microbiology Department for ED SHOs and registrars are well attended with positive feedback. This audit demonstrated that ED staff were most likely to adhere to guidelines when prescribing (79% compliance). Medical SHOs and registrars showed reduced compliance and may benefit from similar dedicated education sessions.